Efficacy and Safety Profile of Suvorexant for the Treatment of Insomnia - Sabat, Ariba; Garg, Aakriti; Khan, Mohd Ashif (Current Drug Safety, 2025)
Insomnia is becoming a concern in general practice as it affects around 30% of adults. It is a sleep disorder characterized by trouble getting asleep, staying asleep, waking up early, and difficulty falling back to sleep. The most commonly used hypnotics, such as benzodiazepines, Z drugs, etc, are associated with various issues, including psychomotor and cognitive impairment. Dual orexin receptor antagonists are an emerging class of hypnotics used to treat insomnia. Suvorexant is a first-in-class dual orexin receptor antagonist approved by the US FDA in 2014 for the treatment of insomnia. Suvorexant is administered orally, absorbed well, metabolized by cytochrome P450 enzyme, and excreted through feces. Some common adverse effects of suvorexant are headache, somnolence, dizziness, diarrhea, cough, abnormal dreams, and upper respiratory tract infection. The current paper aimed to review the pharmacokinetics and pharmacodynamic properties of suvorexant.
Keywords: suvorexant